2020
DOI: 10.1002/jbio.201960210
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of endogenous fluorescence in nonsmall lung cancerous cells: A comparison with nonmalignant lung normal cells

Abstract: Monitoring fluorescence properties of endogenous fluorophores such as nicotinamide adenine dinucleotide (NADH) and flavin adenine dinucleotide (FAD) in normal and cancerous cells provide substantial information noninvasively on biochemical and biophysical aspects of metabolic dysfunction of cancerous cells. Time-resolved spectral profiles and fluorescence lifetime images of NADH and FAD were obtained in human lung nonsmall carcinomas (H661 and A549) and normal lung cells (MRC-5). Both fluorophores show the fas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 73 publications
1
9
0
Order By: Relevance
“…Representative decay profiles obtained as the sum of decay profiles at 21 × 21 pixels and histograms of lifetime distribution are also shown in these figures. As reported in our previous paper, 35 fluorescence decays of FAD of A549, H661, and MCR-5 cells attached on a glass substrate observed in the absence of applied electric field could be analyzed by assuming triexponential decay. In fact, the curve fitting for the observed decay profiles could be done in every case by using a triexponential function, as shown in the Supporting Information (SI) (Figures S1−S3), where the simulated decays are given, together with the residual distribution and the reduced chi-square, χ 2 .…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…Representative decay profiles obtained as the sum of decay profiles at 21 × 21 pixels and histograms of lifetime distribution are also shown in these figures. As reported in our previous paper, 35 fluorescence decays of FAD of A549, H661, and MCR-5 cells attached on a glass substrate observed in the absence of applied electric field could be analyzed by assuming triexponential decay. In fact, the curve fitting for the observed decay profiles could be done in every case by using a triexponential function, as shown in the Supporting Information (SI) (Figures S1−S3), where the simulated decays are given, together with the residual distribution and the reduced chi-square, χ 2 .…”
Section: Resultsmentioning
confidence: 95%
“…Thus, the lung cancerous and normal cells were different in shape from each other, but the autofluorescence spectra of FAD, which were obtained in a suspension of cells, were nearly independent of the cell types (Figure ). Although there was no significant difference in the spectra, the AFL of FAD depended on the cell type . The difference of the lifetime between normal cells and cancerous cells probably originated from the difference in the intracellular environment surrounding fluorophores, which may alter the interaction of FAD cofactor with associated proteins, indicating that AFL imaging of FAD is a sensitive tool to detect such environmental difference. , Then, AFL imaging of FAD was carried out to examine the effects of application of nsPEF(50) on fluorescence characteristics of FAD in these lung cells in relation to field-induced change in intracellular function and mitochondrial function.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…They demonstrated that the fluorescence lifetime of NADH decreases in cancerous tissue. More recently, fluorescence lifetimes of NADH and FAD in human non-small cell lung carcinoma cells have been shown to be significantly shorter than in normal cells using FLIM [ 142 ]. The biochemical basis for these variations is unclear.…”
Section: Time-resolved Fluorescence Spectroscopy and Fluorescence-lifetime Imaging Microscopymentioning
confidence: 99%